2018
DOI: 10.1155/2018/3740395
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Weaning in Stable Heart Transplant Patients: Guidance by Serum Cortisol Level

Abstract: Background Despite earlier studies describing the feasibility of steroid weaning in heart transplant patients, the majority of patients are maintained on steroid therapy for life. We examined a strategy based on a single morning serum cortisol measurement. Methods We assigned stable posttransplant patients, who were maintained on tacrolimus, mycophenolate mofetil, and corticosteroids, into one of two groups based on a screening morning cortisol level. Patients with a cortisol < 8 micrograms/deciliter were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Olivari et al [18] found that 42% of patients receiving standard triple-therapy were successfully withdrawn from CS by 6 months post-HTx. More recently, Baran et al [19] investigated CS weaning in stable HTx recipients by the guidance of morning cortisol. Patients were at least 4 months post-HTx and received tacrolimus-based maintenance therapy.…”
Section: Withdrawal Before 6 Months Post-htxmentioning
confidence: 99%
See 3 more Smart Citations
“…Olivari et al [18] found that 42% of patients receiving standard triple-therapy were successfully withdrawn from CS by 6 months post-HTx. More recently, Baran et al [19] investigated CS weaning in stable HTx recipients by the guidance of morning cortisol. Patients were at least 4 months post-HTx and received tacrolimus-based maintenance therapy.…”
Section: Withdrawal Before 6 Months Post-htxmentioning
confidence: 99%
“…Of patients assigned to steroid weaning, none resumed CS treatment following discontinuation and no episodes of grade ≥2R rejection or unexplained graft dysfunction occurred within a mean follow-up of approximately 10 years. The follow-up time after CS withdrawal differed substantially among studies, ranging from 12 months in a retrospective study [15] to approximately 10 years in both a retrospective and prospective study [16,19]. The International Society for Heart and Lung Transplantation reports a median survival after HTx of 12 years [1], suggesting that longer follow-up time would be advantageous when investigating the long-term effects of CS administration.…”
Section: Withdrawal Before 6 Months Post-htxmentioning
confidence: 99%
See 2 more Smart Citations
“…Adrenal insufficiency after using chronic corticosteroids can be safely monitored in heart transplant patients with serum cortisol and standardized weaning protocols. 21 Most studies have demonstrated comparable survival of patients with a steroid-free regimen. 4,6,7 There are two studies that showed improved survival in patients that were able to tolerate a steroidfree regimen.…”
Section: Weaning Successmentioning
confidence: 99%